기상예보 정보 사용자 그룹의 만족가치 제고 방안 : 강수예보를 중심으로 - 김인겸(In-Gyum Kim); 정지훈(Jihoon Jung); 김정윤(Jeong-Yun Kim); 신진호(Jinho Shin); 김백조(Baek-Jo Kim); 이기광(Ki-Kwang Lee) (한국콘텐츠학회 논문지, 13(11), 2013)
The providers of meteorological information want to know the level of satisfaction of forecast users with their services. To provide better service, meteorological communities of each nation are administering a survey on satisfaction of forecast users. However, most researchers provided these users with simple questionnaires and the respondents had to choose one answer among different satisfaction levels. So, the results of this kind of survey have low explanation power and are difficult to use in developing strategy of forecast service. In this study, instead of cost-loss concept, we applied satisfaction-dissatisfaction concept to the $2{×}2$ contingency table, which is a useful tool to evaluate value of forecast, and estimated satisfaction value of 24h precipitation forecasts in Shanghai, China and Seoul, Korea. Moreover, not only the individual satisfaction value of forecast but the user group's satisfaction value was evaluated. As for the result, it is effective to enhance forecast accuracy to improve the satisfaction value of deterministic forecast user group, but in the case of probabilistic forecast, it is important to know the level of dissatisfaction of user group and distribution of probability threshold of forecast users. These results can help meteorological communities to search for a solution which can provide better satisfaction value to forecast users. 기상정보 제공자들은 예보사용자들이 제공되는 예보서비스에 얼마나 만족하고 있는지를 알고 싶어 한다. 더 나은 예보서비스 제공을 위해서 각국의 기상 커뮤니티들은 사용자들의 만족도에 관한 다양한 설문조사를 진행하고 있다. 하지만 대부분의 설문조사들이 단순하게 사용자들이 얼마나 서비스에 만족하는지를 질문하고 있기 때문에 설문 결과의 설명력이 떨어지고, 예보서비스의 전략수립에 활용되기 어렵다. 본 연구에서는 예보의 가치를 평가하는 유용한 도구인 $2{×}2$ 검증테이블에 기존의 비용-손실이 아닌 만족-불만족 개념을 적용하여 상해와 서울에서 제공된 24시간 강수예보의 만족가치를 도출하였다. 그리고 예보에 대한 개인의 만족가치뿐만 아니라 예보 사용자 그룹의 만족가치를 평가하였다. 그 결과, 확정예보 사용자 그룹의 만족가치를 높이기 위해선 예보 정확도의 향상이 유용하지만, 확률예보의 경우엔 사용자 그룹의 불만족 정도와 예보확률의 사용 분포를 파악하는 것이 중요한 것으로 나타났다. 따라서 기상 커뮤니티들이 예보 사용자들에게 더 나은 만족가치를 제공할 수 있는 방안을 찾는데 도움을 줄 수 있을 것이다.